Empowering Local SMEs in Rural Java through a Community-Based E-Commerce Training and Digital Literacy Program - Edi Supardi; Amin Zaki; Nina Anis; Dikky Suryadi (Yayasan Adra Karima Hubbi, 2025)
Background. Rural micro, small, and medium enterprises (SMEs) in Java remain economically marginalized due to low digital literacy, limited market access, and minimal use of e-commerce platforms. Although digital transformation initiatives have been introduced nationally, a digital divide between rural and urban areas persists, reducing SME competitiveness and weakening rural economic resilience. Purpose. The study aims to assess digital literacy needs among rural SMEs, implement a collaborative community-based digital training model, and evaluate the measurable impacts of the program on e-commerce adoption and business growth. Method. A mixed-methods research approach was used, combining pre- and post-training surveys, direct observation, focus group discussions, and business performance tracking. The intervention lasted 12 weeks and involved 50 SME participants from three rural villages in Java. Results. The study found notable improvements in participants’ digital skills, especially in online marketing, secure digital transactions, and the use of social commerce platforms. SMEs also experienced increased customer engagement and moderate revenue growth. Community participation further strengthened peer learning and supported ongoing knowledge retention. Conclusion. A community-based digital literacy model is effective and scalable for reducing digital gaps in rural areas. By empowering SMEs as active digital participants, the program enhances inclusive digital economic development and supports broader rural socio-economic advancement.